Sodium hypochlorite production process based on supported catalyst and adsorbent

By using a supported catalyst-coated titanium-based material as anode in the sodium hypochlorite production process, and purifying it with modified activated carbon adsorption impurities and double-stage membrane separation technology, the problem of easy corrosion and low purification efficiency of anode materials in the traditional process is solved, and efficient and stable production of sodium hypochlorite is achieved.

CN119615188APending Publication Date: 2025-03-14TIANJIN TAISHIKANG PHARMA SCI TECHNIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411795654.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the traditional sodium hypochlorite production process, the anode material is prone to corrosion, the impurities in the electrolyte are difficult to remove, and the purification efficiency is low, which affects product quality and equipment life.

Method used

The titanium-based material coated with supported catalysts is used as the anode, combined with modified activated carbon to adsorb impurities, and is efficiently purified by double-stage membrane separation technology, and finally a combination of stabilizers is added to improve product stability.

Benefits of technology

It improves electrode stability and catalytic efficiency, effectively removes impurities, achieves efficient purification, and improves product stability and quality consistency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of sodium hypochlorite production, in particular to a sodium hypochlorite production process based on a supported catalyst and an adsorbent, which comprises the following steps: providing an aqueous solution containing sodium chloride as a reaction raw material, filtering and degassing the aqueous solution, and then introducing the aqueous solution into an electrolytic bath for electrolysis, a titanium-based material coated with a supported catalyst is used as an anode, modified activated carbon is added to adsorb impurities, a two-stage membrane separation technology is used for purification, and finally a stabilizer combination is added. According to the process, the electrode stability and catalytic efficiency are improved by using a supported catalyst, impurities are effectively removed through modified activated carbon, efficient purification is realized by adopting a two-stage membrane separation technology, the product stability is improved by adding a stabilizer combination, and meanwhile, the consistency of product quality is ensured by accurately controlling electrolysis conditions; the method has the advantages that the electrode stability and catalytic efficiency are improved, impurities are effectively removed, efficient purification is achieved, and the product stability and quality consistency are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium hypochlorite production, and in particular to a sodium hypochlorite production process based on a supported catalyst and an adsorbent. Background Art

[0002] At present, sodium hypochlorite is an important chemical product, widely used in water treatment, disinfection, bleaching and other fields. The traditional production process of sodium hypochlorite mainly adopts the sodium chloride electrolysis method, but there are some problems. First, the anode material used in the electrolysis process is susceptible to corrosion, which affects the product quality and equipment life. Secondly, impurities such as organic matter and heavy metal ions will be produced in the electrolyte, reducing the purity of the product. In addition, the purification process in the traditional process is inefficient and it is difficult to effectively remove excess salt and small molecule impurities.

[0003] To solve these problems, the researchers proposed an improved sodium hypochlorite production process. This process uses a titanium-based material coated with a supported catalyst as the anode, which improves the stability and catalytic efficiency of the electrode. At the same time, by adding modified activated carbon to the electrolyte, the organic matter and heavy metal ion impurities generated during the electrolysis process can be effectively adsorbed and removed. In addition, the process also introduces a two-stage membrane separation technology, which achieves efficient purification of the electrolyte through the combination of ultrafiltration membrane and nanofiltration membrane.

[0004] However, the existing improved processes still have some shortcomings. For example, the preparation method and loading process of the supported catalyst need to be further optimized to improve the performance and stability of the catalyst. The preparation process of modified activated carbon also needs more precise control to obtain better adsorption effect. In addition, there is still room for improvement in the parameter control of the two-stage membrane separation technology and the maintenance of the membrane components to improve the purification efficiency and extend the service life of the membrane.

[0005] In this regard, the present application specifically proposes a sodium hypochlorite production process based on a supported catalyst and an adsorbent to solve the above technical problems. Summary of the invention

[0006] The invention provides a sodium hypochlorite production process based on a supported catalyst and an adsorbent, which has the advantages of improving electrode stability and catalytic efficiency, effectively removing impurities, achieving efficient purification, and improving product stability and quality consistency.

[0007] The technical solution adopted by the present invention to solve the above technical problems is: a sodium hypochlorite production process based on a supported catalyst and an adsorbent, comprising the following steps:

[0008] Step 1: providing an aqueous solution containing sodium chloride as a reaction raw material;

[0009] Step 2: filtering and degassing the sodium chloride aqueous solution to remove impurities and dissolved gases therein;

[0010] Step 3: introducing the treated sodium chloride aqueous solution into an electrolytic cell, applying direct current between the anode and the cathode, wherein the anode is a titanium-based material coated with a supported catalyst, and the cathode is a stainless steel or nickel-based material;

[0011] Step 4: During the electrolysis process, chloride ions in the sodium chloride aqueous solution are oxidized into chlorine gas at the anode, and then the chlorine gas dissolves in water to form hypochlorous acid, which further generates sodium hypochlorite;

[0012] Step 5: adding modified activated carbon to the electrolyte to adsorb and remove organic matter and heavy metal ion impurities generated during the electrolysis process, wherein the modified activated carbon is obtained by modifying coconut shell activated carbon with concentrated nitric acid, and the nitric acid accounts for 30% to 60% of the mass of the coconut shell activated carbon;

[0013] Step 6: Cooling the electrolyte containing sodium hypochlorite and further purifying it by a two-stage membrane separation technology, wherein the first-stage membrane uses an ultrafiltration membrane with a molecular weight cutoff of 1000 to 20000 Daltons to remove macromolecular impurities, and the replacement frequency of the ultrafiltration membrane is controlled by online monitoring of the conductivity of the electrolyte to ensure the performance and stability of the membrane assembly, and the second-stage membrane uses a nanofiltration membrane with a molecular weight cutoff of 150 to 500 Daltons to remove excess salt and other small molecular impurities, and the target value of removing salt is 50% to 70%, thereby obtaining a sodium hypochlorite electrolyte;

[0014] Step 7: Filter the purified sodium hypochlorite solution through a sterile filter to obtain a final product; at the same time, add a specific stabilizer combination to the finished product to improve the stability of the sodium hypochlorite solution.

[0015] Furthermore, the supported catalyst is a mixture of ruthenium dioxide and tin dioxide, with a mass ratio of 1:1 to 3:1, and is uniformly loaded on the titanium-based material through PECVD technology, with the loading amount being 0.5% to 5% of the total mass of the titanium-based material, and the thickness and uniformity of the catalyst layer are optimized by controlling the PECVD process parameters.

[0016] Furthermore, the PECVD process uses Ar plasma to bombard the surface of the titanium-based material to form a porous structure on the surface, and then adsorbs the precursor solution of ruthenium dioxide and tin dioxide, including using a double pulse method to alternately apply voltage and connect Ar gas, wherein the voltage is set to 500V to 700V, and the Ar gas flow rate is set to 15sccm to 25sccm. During the application of voltage, the plasma power is 300W to 400W, and Ru chloride and Sn chlorate are introduced at the same time, wherein the Ru chloride is selected from ruthenium chloride, and the Sn chlorate is selected from tin chlorate, and the mass ratio of tin chlorate to ruthenium chloride is 1:1 to 1:3.

[0017] Furthermore, the modified activated carbon is obtained by modifying coconut shell activated carbon with concentrated nitric acid, the concentration of the concentrated nitric acid is 36% to 70%, and the amount of the concentrated nitric acid used is 25% to 50% of the mass of the coconut shell activated carbon to obtain the modified activated carbon.

[0018] Furthermore, the first-stage membrane of the two-stage membrane separation technology adopts an ultrafiltration membrane with a pore size of 0.01 microns to 0.1 microns, and the second-stage membrane adopts a nanofiltration membrane with a molecular weight cutoff of 150 Daltons to 500 Daltons. The replacement frequency of the ultrafiltration membrane is controlled by online monitoring of the conductivity of the electrolyte, and the purification process of the electrolyte is controlled by controlling the flow rate of the first-stage ultrafiltration membrane and the second-stage nanofiltration membrane.

[0019] Furthermore, the current density of the electrolysis process is 100A / m 2 Up to 300A / m 2 The electrolysis temperature is controlled between 25°C and 45°C, and the pH value and temperature during the electrolysis process are monitored by a real-time monitoring system to automatically adjust the electrolysis conditions.

[0020] Furthermore, a diaphragm with a thickness of 30 to 80 microns is provided between the anode and cathode of the electrolytic cell, and the diaphragm is a perfluorocarboxylic acid ion exchange membrane, which is used to prevent direct contact between the anode and cathode and improve electrolysis efficiency.

[0021] Furthermore, the specific stabilizer combination includes a mixture of phosphate, carbonate and silicate, and the mass ratio of phosphate, carbonate and silicate is 1:1:1.

[0022] Furthermore, the method of modifying coconut shell activated carbon by concentrated nitric acid in step 5 comprises the following steps: a. stirring and mixing coconut shell activated carbon particles and a modifier aqueous solution, with a solid-liquid ratio of 1:10 to 1:8 and a temperature of the modifier aqueous solution of 15°C to 45°C; b. treating the stirred and mixed solution at a pressure of 0.2 MPa to 0.5 MPa for 1.5 hours to 4 hours; c. filtering the modified solution and washing it with deionized water until it is neutral to obtain modified activated carbon.

[0023] The advantages of the present invention are: the present invention provides a sodium hypochlorite production process based on a supported catalyst and an adsorbent, which has the following advantages:

[0024] The present invention provides a sodium hypochlorite production process based on a supported catalyst and an adsorbent, comprising providing an aqueous solution containing sodium chloride as a reaction raw material, filtering and degassing the aqueous solution, then introducing the aqueous solution into an electrolytic cell for electrolysis, using a titanium-based material coated with a supported catalyst as an anode, adding modified activated carbon to adsorb impurities, purifying the aqueous solution by a two-stage membrane separation technology, and finally adding a stabilizer combination. This process improves electrode stability and catalytic efficiency by using a supported catalyst, effectively removes impurities by using modified activated carbon, achieves efficient purification by using a two-stage membrane separation technology, and improves product stability by adding a stabilizer combination. At the same time, the consistency of product quality is ensured by precisely controlling the electrolysis conditions, and has the advantages of improving electrode stability and catalytic efficiency, effectively removing impurities, achieving efficient purification, and improving product stability and quality consistency. DETAILED DESCRIPTION

[0025] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Embodiment 1:

[0027] The present invention proposes a sodium hypochlorite production process based on a supported catalyst and an adsorbent, comprising the following steps:

[0028] An aqueous solution containing sodium chloride is provided as a reaction raw material; the sodium chloride aqueous solution is filtered and degassed to remove impurities and dissolved gases therein; the treated sodium chloride aqueous solution is introduced into an electrolytic cell, and direct current is applied between an anode and a cathode, wherein the anode is a titanium-based material coated with a supported catalyst, and the cathode is a stainless steel or nickel-based material; during the electrolysis process, chloride ions in the sodium chloride aqueous solution are oxidized into chlorine gas at the anode, and then the chlorine gas dissolves in water to form hypochlorous acid, and further generates sodium hypochlorite; organic matter and heavy metal ion impurities generated during the electrolysis process are adsorbed and removed by adding modified activated carbon to the electrolyte, wherein the modified activated carbon is obtained by modifying coconut shell activated carbon with concentrated nitric acid, and the nitric acid accounts for 30% to 60% of the mass of the coconut shell activated carbon; The electrolyte containing sodium hypochlorite is cooled and further purified by a two-stage membrane separation technology. The first-stage membrane uses an ultrafiltration membrane with a molecular weight cutoff of 1000 Daltons to 20000 Daltons to remove large molecular impurities. The replacement frequency of the ultrafiltration membrane is controlled by online monitoring of the conductivity of the electrolyte to ensure the performance and stability of the membrane component. The second-stage membrane uses a nanofiltration membrane with a molecular weight cutoff of 150 Daltons to 500 Daltons to remove excess salt and other small molecular impurities. The target value of removing salt is 50% to 70%, and a sodium hypochlorite electrolyte is obtained; the purified sodium hypochlorite solution is filtered through a sterile filter to obtain a final product; at the same time, a specific stabilizer combination is added to the finished product to improve the stability of the sodium hypochlorite solution.

[0029] Wherein, the supported catalyst can be a mixture of ruthenium dioxide and tin dioxide, the mass ratio between the two is 1:1 to 3:1, and is uniformly loaded on the titanium-based material by PECVD technology, the loading amount is 0.5% to 5% of the total mass of the titanium-based material, and the thickness and uniformity of the catalyst layer are optimized by controlling the PECVD process parameters. The PECVD process uses Ar plasma to bombard the surface of the titanium-based material to form a porous structure on the surface, and then adsorbs the precursor solution of ruthenium dioxide and tin dioxide, including alternately applying voltage and connecting Ar gas by a double pulse method, wherein the voltage is set to 500V to 700V, and the Ar gas flow rate is set to 15sccm to 25sccm. During the application of voltage, the plasma power is 300W to 400W, and Ru chloride and Sn chlorate are introduced at the same time, wherein the Ru chloride is selected from ruthenium chloride, and the Sn chlorate is selected from tin chlorate, and the mass ratio of tin chlorate to ruthenium chloride is 1:1 to 1:3.

[0030] Furthermore, the modified activated carbon is obtained by modifying coconut shell activated carbon with concentrated nitric acid, the concentration of concentrated nitric acid is 36% to 70%, and the amount of concentrated nitric acid used is 25% to 50% of the mass of coconut shell activated carbon to obtain modified activated carbon. The first stage membrane of the two-stage membrane separation technology adopts an ultrafiltration membrane with a pore size of 0.01 micron to 0.1 micron, and the second stage adopts a nanofiltration membrane with a molecular weight cutoff of 150 Dalton to 500 Dalton. The replacement frequency of the ultrafiltration membrane is controlled by online monitoring of the conductivity of the electrolyte, and the purification process of the electrolyte is controlled by controlling the flow rate of the first stage ultrafiltration membrane and the second stage nanofiltration membrane. The current density of the electrolysis process is 100A / m 2 Up to 300A / m 2 The electrolysis temperature is controlled between 25°C and 45°C, and the pH value and temperature during the electrolysis process are monitored by a real-time monitoring system to automatically adjust the electrolysis conditions. A diaphragm with a thickness of 30 to 80 microns is provided between the anode and cathode of the electrolytic cell. The diaphragm is a perfluorocarboxylic acid ion exchange membrane, which is used to prevent direct contact between the anode and cathode and improve the electrolysis efficiency. The specific stabilizer combination includes a mixture of phosphates, carbonates and silicates, and the mass ratio of phosphates, carbonates and silicates is 1:1:1.

[0031] Specifically, the method for modifying coconut shell activated carbon by concentrated nitric acid includes the following steps: stirring and mixing coconut shell activated carbon particles with a modifier aqueous solution at a solid-liquid ratio of 1:10 to 1:8, and the temperature of the modifier aqueous solution is 15°C to 45°C, and the stirred and mixed solution is treated at a pressure of 0.2 MPa to 0.5 MPa for 1.5 hours to 4 hours; the modified solution is filtered and washed with deionized water until neutral to obtain modified activated carbon.

[0032] Therefore, the process of the present application achieves efficient production and purification of sodium hypochlorite by optimizing electrolysis conditions, using efficient supported catalysts and modified activated carbon adsorbents, and adopting dual-stage membrane separation technology. Compared with the prior art, the process of the present application can more effectively remove impurities, improve the purity and stability of sodium hypochlorite, and ensure the stability and controllability of the production process by real-time monitoring and automatic adjustment of electrolysis conditions.

[0033] Furthermore, the present application also proposes that the supported catalyst is a mixture of ruthenium dioxide and tin dioxide, with a mass ratio of 1:1 to 3:1, and is uniformly loaded on the titanium-based material through PECVD technology, with a loading amount of 0.5% to 5% of the total mass of the titanium-based material, and the thickness and uniformity of the catalyst layer are optimized by controlling the PECVD process parameters.

[0034] Among them, the PECVD technology uses Ar plasma to bombard the surface of the titanium-based material to form a porous structure on the surface, and then adsorbs the precursor solution of ruthenium dioxide and tin dioxide. Specifically, a double pulse method is used to alternately apply voltage and connect Ar gas, wherein the voltage is set to 500V to 700V, and the Ar gas flow rate is set to 15sccm to 25sccm. During the application of voltage, the plasma power is 300W to 400W, and a chloride containing Ru and a chlorate of Sn are introduced at the same time, wherein the chloride of Ru is selected from ruthenium chloride, and the chlorate of Sn is selected from tin chlorate, and the mass ratio of tin chlorate to ruthenium chloride is 1:1 to 1:3. As a preferred embodiment, the voltage can be set to 600V, the Ar gas flow rate is 20sccm, the plasma power is 350W, and the mass ratio of tin chlorate to ruthenium chloride is 1:2.

[0035] Therefore, by using PECVD technology to uniformly load a mixture of ruthenium dioxide and tin dioxide on the titanium-based material, not only the activity of the catalyst is improved, but also the stability and uniformity of the catalyst layer are enhanced. Specifically, this technical means solves the problem of uneven catalyst layer and low activity in the prior art, improves the efficiency of chloride ion oxidation during electrolysis, and thus improves the production efficiency and product quality of sodium hypochlorite.

[0036] Furthermore, the present application also proposes that Ar plasma is used to bombard the surface of the titanium-based material in the PECVD process to form a porous structure on the surface, and then the precursor solution of ruthenium dioxide and tin dioxide is adsorbed. Specifically, a double pulse method is used to alternately apply voltage and connect Ar gas, wherein the voltage is set to 500V to 700V, and the Ar gas flow rate is set to 15sccm to 25sccm. During the application of voltage, the plasma power is 300W to 400W, and a chloride containing Ru and a chlorate of Sn are introduced at the same time. Among them, the chloride of Ru is selected from ruthenium chloride, and the chlorate of Sn is selected from tin chlorate, and the mass ratio of tin chlorate to ruthenium chloride is 1:1 to 1:3.

[0037] As a preferred embodiment, Ar plasma bombarding the surface of the titanium-based material can form a uniform porous structure, which helps to improve the loading efficiency and uniformity of the catalyst. The use of the double pulse method can effectively control the voltage and the on-off of the Ar gas, thereby optimizing the generation of plasma and the adsorption process of the catalyst precursor. In addition, by adjusting the voltage, Ar gas flow rate and plasma power, the thickness and uniformity of the catalyst layer can be further optimized to ensure the effective loading of the catalyst on the titanium-based material.

[0038] Therefore, through the Ar plasma bombardment and double pulse method in the PECVD process, it is possible to achieve uniform loading of ruthenium dioxide and tin dioxide on the titanium-based material, thereby improving the activity and stability of the catalyst. Specifically, this technical solution solves the problem of uneven activity and easy deactivation of traditional supported catalysts during the electrolysis process, and improves the efficiency of the sodium hypochlorite production process and product quality.

[0039] Furthermore, the present application also proposes that the modified activated carbon is obtained by modifying coconut shell activated carbon with concentrated nitric acid, the concentration of concentrated nitric acid is 36% to 70%, and the amount of concentrated nitric acid used is 25% to 50% of the mass of coconut shell activated carbon to obtain modified activated carbon.

[0040] Among them, the concentration range of concentrated nitric acid is 36% to 70%. Nitric acid of this concentration can effectively react chemically with coconut shell activated carbon, change its surface properties, and thus improve its adsorption capacity. Furthermore, the amount of concentrated nitric acid used accounts for 25% to 50% of the mass of coconut shell activated carbon, and this ratio ensures the adequacy and effectiveness of the modification process. Specifically, the reaction of concentrated nitric acid with coconut shell activated carbon can be carried out at room temperature or under heating conditions to accelerate the reaction process. As a preferred embodiment, the modification process can be carried out under stirring conditions to ensure uniform contact between concentrated nitric acid and coconut shell activated carbon. As a result, the modified activated carbon has a higher adsorption efficiency and can more effectively remove organic matter and heavy metal ion impurities generated during the electrolysis process.

[0041] The above technical solution is briefly and in-depth summarized. The technical solution solves the technical problem of improving the adsorption efficiency of activated carbon by modifying coconut shell activated carbon with concentrated nitric acid of a specific concentration. Specifically, the chemical modification of concentrated nitric acid can significantly improve the surface properties of coconut shell activated carbon, making it have a stronger adsorption capacity in the electrolyte. Compared with the prior art, the advantage of this technical solution is that by accurately controlling the concentration and usage of concentrated nitric acid, efficient modification of activated carbon is achieved, thereby improving the overall efficiency and product quality of the sodium hypochlorite production process.

[0042] Furthermore, the present application also proposes that in the sodium hypochlorite production process, a two-stage membrane separation technology is used to purify the electrolyte. Specifically, the first-stage membrane uses an ultrafiltration membrane with a pore size of 0.01 microns to 0.1 microns to remove macromolecular impurities. The replacement frequency of the ultrafiltration membrane is controlled by online monitoring of the conductivity of the electrolyte to ensure the performance and stability of the membrane assembly. The second-stage membrane uses a nanofiltration membrane with a molecular weight cutoff of 150 Daltons to 500 Daltons to remove excess salt and other small molecule impurities, and the target value for removing salt is 50% to 70%.

[0043] Among them, the pore size selection range of the ultrafiltration membrane is 0.01 micron to 0.1 micron, which can effectively remove large molecular impurities in the electrolyte while maintaining the fluidity and treatment efficiency of the electrolyte. The molecular weight cutoff selection range of the nanofiltration membrane is 150 Dalton to 500 Dalton, which can effectively remove small molecular impurities and excess salt in the electrolyte, thereby improving the purity of the sodium hypochlorite electrolyte. Furthermore, by controlling the flow rate of the first-stage ultrafiltration membrane and the second-stage nanofiltration membrane, the purification process of the electrolyte can be optimized to ensure the purity and treatment efficiency of the electrolyte.

[0044] Therefore, the technical solution of the present application can effectively remove macromolecular and small molecular impurities in the electrolyte through the double-stage membrane separation technology, and improve the purity of the sodium hypochlorite electrolyte. Compared with the prior art, the technical solution of the present application has higher purification efficiency and better stability, and can effectively solve the problem of high impurity content in the electrolyte, thereby improving the quality and production efficiency of the sodium hypochlorite product.

[0045] Furthermore, the present application also proposes that the current density of the electrolysis process is 100A / m 2 Up to 300A / m 2 The electrolysis temperature is controlled between 25°C and 45°C, and the pH value and temperature during the electrolysis process are monitored by a real-time monitoring system to automatically adjust the electrolysis conditions.

[0046] Specifically, current density refers to the current intensity per unit area. By controlling the current density, the energy consumption and product generation rate in the electrolysis process can be optimized. The electrolysis temperature directly affects the rate and efficiency of the electrolysis reaction. By controlling it between 25°C and 45°C, it can be ensured that the electrolysis reaction is carried out within the optimal temperature range. The real-time monitoring system is used to monitor the pH value and temperature during the electrolysis process. Changes in these parameters can reflect the progress of the electrolysis reaction. By automatically adjusting the electrolysis conditions, such as adjusting the current density and temperature, the stability and efficiency of the electrolysis process can be ensured.

[0047] As a preferred embodiment, the real-time monitoring system may include a pH sensor and a temperature sensor, which transmit real-time data to a control system, and the control system automatically adjusts the electrolysis conditions according to a preset parameter range. For example, when the pH value deviates from the optimal range, the control system can automatically adjust the composition or flow rate of the electrolyte to restore the optimal pH value. Similarly, when the temperature is too high or too low, the control system can adjust the temperature of the electrolytic cell through a cooling or heating device.

[0048] Therefore, by precisely controlling the current density and temperature during the electrolysis process, combined with real-time monitoring and automatic adjustment systems, the efficiency and stability of sodium hypochlorite production can be significantly improved, and energy consumption and production costs can be reduced. Compared with the prior art, the technical solution of the present application can more effectively control the electrolysis process, ensuring the consistency of product quality and the stability of the production process.

[0049] Furthermore, the present application also proposes that a diaphragm with a thickness of 30 to 80 microns is provided between the anode and cathode of the electrolytic cell, and the diaphragm is a perfluorocarboxylic acid ion exchange membrane, which is used to prevent direct contact between the anode and cathode and improve the electrolysis efficiency.

[0050] Specifically, the perfluorocarboxylic acid ion exchange membrane has excellent chemical stability and mechanical strength, and can effectively isolate the anode and cathode during the electrolysis process to prevent short circuits between the electrodes. In addition, the selective permeability of the membrane helps to improve electrolysis efficiency and reduce energy losses. As a preferred embodiment, the thickness of the diaphragm is controlled between 30 microns and 80 microns, which can ensure sufficient mechanical strength and efficient ion transmission.

[0051] Therefore, by setting a perfluorocarboxylic acid ion exchange membrane in the electrolytic cell, the technical solution of the present application effectively solves the short circuit problem caused by direct contact between the anode and the cathode during the electrolysis process, improves the electrolysis efficiency, and reduces energy loss. Compared with the prior art, the technical solution of the present application has significant advantages in improving electrolysis efficiency and stability.

[0052] Furthermore, the present application also proposes that, in the process of producing sodium hypochlorite solution, in order to improve the stability of the product, a specific stabilizer combination is added to the final product. The stabilizer combination includes a mixture of phosphate, carbonate and silicate, wherein the mass ratio of phosphate, carbonate and silicate is 1:1:1.

[0053] Specifically, the mixture of phosphate, carbonate and silicate can be prepared in a variety of ways. For example, sodium dihydrogen phosphate, sodium carbonate and sodium silicate can be mixed in a mass ratio of 1:1:1, and then dried and ground under appropriate temperature and humidity conditions to obtain the desired stabilizer combination. In addition, the mixture can also be directly synthesized by chemical reaction, in which the precursors of phosphate, carbonate and silicate react in proportion under reaction conditions to generate the target product.

[0054] Therefore, by adding this specific stabilizer combination, the stability of the sodium hypochlorite solution can be effectively improved to prevent it from decomposing or failing during storage and use. This technical solution not only solves the problem that the sodium hypochlorite solution is prone to failure during long-term storage, but also improves the service life and safety of the product. Compared with the prior art, the technical solution of the present application has higher stability and longer validity period, thus having significant advantages in practical applications.

[0055] Furthermore, the present application also proposes that the method for modifying coconut shell activated carbon by concentrated nitric acid comprises the following steps: a. stirring and mixing coconut shell activated carbon particles with a modifier aqueous solution at a solid-liquid ratio of 1:10 to 1:8 and a modifier aqueous solution temperature of 15°C to 45°C; b. treating the stirred and mixed solution at a pressure of 0.2 MPa to 0.5 MPa for 1.5 hours to 4 hours; c. filtering the modified solution and washing it with deionized water until it is neutral to obtain modified activated carbon.

[0056] Among them, the temperature of the modifier aqueous solution and the solid-liquid ratio can be adjusted according to actual needs to achieve the best modification effect. Specifically, the choice of temperature and solid-liquid ratio will affect the contact and reaction efficiency between the modifier and the coconut shell activated carbon particles, thereby affecting the adsorption performance of the modified activated carbon. Furthermore, the choice of treatment pressure and time are also key factors, which determine the penetration depth and uniformity of the modifier in the coconut shell activated carbon particles. For example, higher pressure and longer treatment time can increase the penetration depth of the modifier, but may also increase production costs and energy consumption.

[0057] As a preferred embodiment, the temperature of the aqueous solution of the modifier can be set to 30°C, the solid-liquid ratio to 1:9, the treatment pressure to 0.3 MPa, and the treatment time to 2.5 hours. The modified activated carbon thus obtained has a higher adsorption efficiency and a longer service life.

[0058] The above technical solution is briefly and in-depth summarized. This technical solution solves the problems of adsorption efficiency and service life in the modification process of coconut shell activated carbon by optimizing the temperature, solid-liquid ratio, processing pressure and time of the modifier aqueous solution. Specifically, by controlling these parameters, the uniform distribution and deep penetration of the modifier in the coconut shell activated carbon particles can be ensured, thereby improving its ability to adsorb organic matter and heavy metal ions. Compared with the existing technology, this technical solution has higher modification efficiency and better modification effect, and can significantly improve the purity and stability of the electrolyte in the sodium hypochlorite production process.

[0059] Furthermore, the present application also proposes that in the sodium hypochlorite production process, a diaphragm with a thickness of 30 to 80 microns is provided between the anode and cathode of the electrolytic cell, and the diaphragm is a perfluorocarboxylic acid ion exchange membrane, which is used to prevent direct contact between the anode and the cathode and improve the electrolysis efficiency. Specifically, the setting of the diaphragm can effectively isolate the anode and the cathode, prevent the direct mixing of chlorine and hydrogen generated during the electrolysis process, thereby avoiding possible explosion risks. In addition, the perfluorocarboxylic acid ion exchange membrane has excellent chemical stability and electrical conductivity, and can maintain efficient ion transmission during the electrolysis process, further improving the electrolysis efficiency.

[0060] The thickness of the diaphragm can be controlled by adjusting the manufacturing process parameters, such as by controlling the coating thickness of the diaphragm material or by stacking multiple layers. Furthermore, the material selection of the diaphragm can also be optimized according to actual application requirements, such as selecting a material with higher corrosion resistance and mechanical strength to extend the service life of the diaphragm.

[0061] Therefore, by setting a perfluorocarboxylic acid ion exchange membrane in the electrolytic cell, the sodium hypochlorite production process of the present application not only improves the electrolysis efficiency, but also enhances the safety of the production process. Specifically, this technical solution solves the potential safety hazards caused by direct contact between the anode and cathode of the electrolytic cell in the prior art, and further improves the stability and efficiency of the electrolysis process by optimizing the diaphragm material and thickness. Compared with the prior art, the technical solution of the present application significantly reduces the safety risks in the production process while improving production efficiency, and has significant technical advantages.

[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some or all of the technical features therein can be replaced by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A sodium hypochlorite production process based on a supported catalyst and an adsorbent, characterized in that: The following steps are involved: Step 1: providing an aqueous solution containing sodium chloride as a reaction raw material; Step 2: filtering and degassing the sodium chloride aqueous solution to remove impurities and dissolved gases therein; Step 3: introducing the treated sodium chloride aqueous solution into an electrolytic cell, applying direct current between the anode and the cathode, wherein the anode is a titanium-based material coated with a supported catalyst, and the cathode is a stainless steel or nickel-based material; Step 4: During the electrolysis process, chloride ions in the sodium chloride aqueous solution are oxidized into chlorine gas at the anode, and then the chlorine gas dissolves in water to form hypochlorous acid, which further generates sodium hypochlorite; Step 5: adding modified activated carbon to the electrolyte to adsorb and remove organic matter and heavy metal ion impurities generated during the electrolysis process, wherein the modified activated carbon is obtained by modifying coconut shell activated carbon with concentrated nitric acid, and the nitric acid accounts for 30% to 60% of the mass of the coconut shell activated carbon; Step 6: Cooling the electrolyte containing sodium hypochlorite and further purifying it by a two-stage membrane separation technology, wherein the first-stage membrane uses an ultrafiltration membrane with a molecular weight cutoff of 1000 to 20000 Daltons to remove macromolecular impurities, and the replacement frequency of the ultrafiltration membrane is controlled by online monitoring of the conductivity of the electrolyte to ensure the performance and stability of the membrane assembly, and the second-stage membrane uses a nanofiltration membrane with a molecular weight cutoff of 150 to 500 Daltons to remove excess salt and other small molecular impurities, and the target value of removing salt is 50% to 70%, thereby obtaining a sodium hypochlorite electrolyte; Step 7: Filter the purified sodium hypochlorite solution through a sterile filter to obtain a final product; at the same time, add a specific stabilizer combination to the finished product to improve the stability of the sodium hypochlorite solution.

2. A sodium hypochlorite production process based on a supported catalyst and an adsorbent according to claim 1, characterized in that: The supported catalyst is a mixture of ruthenium dioxide and tin dioxide, with a mass ratio of 1:1 to 3:1, and is uniformly supported on a titanium-based material by PECVD technology, with a loading amount of 0.5% to 5% of the total mass of the titanium-based material, and the thickness and uniformity of the catalyst layer are optimized by controlling PECVD process parameters.

3. A sodium hypochlorite production process based on a supported catalyst and an adsorbent according to claim 2, characterized in that: The PECVD process uses Ar plasma to bombard the surface of the titanium-based material to form a porous structure on the surface, and then adsorbs the precursor solution of ruthenium dioxide and tin dioxide, including using a double pulse method to alternately apply voltage and connect Ar gas, wherein the voltage is set to 500V to 700V, and the Ar gas flow rate is set to 15sccm to 25sccm. During the application of voltage, the plasma power is 300W to 400W, and Ru chloride and Sn chlorate are introduced at the same time, wherein the Ru chloride is selected from ruthenium chloride, and the Sn chlorate is selected from tin chlorate, and the mass ratio of tin chlorate to ruthenium chloride is 1:1 to 1:

3.

4. A sodium hypochlorite production process based on a supported catalyst and an adsorbent according to claim 1, characterized in that: The modified activated carbon is obtained by modifying coconut shell activated carbon with concentrated nitric acid, the concentration of the concentrated nitric acid is 36% to 70%, and the amount of the concentrated nitric acid used is 25% to 50% of the mass of the coconut shell activated carbon to obtain the modified activated carbon.

5. A sodium hypochlorite production process based on a supported catalyst and an adsorbent according to claim 1, characterized in that: The first-stage membrane of the dual-stage membrane separation technology adopts an ultrafiltration membrane with a pore size of 0.01 microns to 0.1 microns, and the second-stage adopts a nanofiltration membrane with a molecular weight cutoff of 150 Daltons to 500 Daltons. The replacement frequency of the ultrafiltration membrane is controlled by online monitoring of the conductivity of the electrolyte, and the purification process of the electrolyte is controlled by controlling the flow rate of the first-stage ultrafiltration membrane and the second-stage nanofiltration membrane.

6. A sodium hypochlorite production process based on a supported catalyst and an adsorbent according to claim 1, characterized in that: The current density of the electrolysis process is 100A / m 2 Up to 300A / m 2 The electrolysis temperature is controlled between 25°C and 45°C, and the pH value and temperature during the electrolysis process are monitored by a real-time monitoring system to automatically adjust the electrolysis conditions.

7. A sodium hypochlorite production process based on a supported catalyst and an adsorbent according to claim 1, characterized in that: A diaphragm with a thickness of 30 to 80 microns is arranged between the anode and cathode of the electrolytic cell. The diaphragm is a perfluorocarboxylic acid ion exchange membrane, which is used to prevent direct contact between the anode and cathode and improve electrolysis efficiency.

8. A sodium hypochlorite production process based on a supported catalyst and an adsorbent according to claim 1, characterized in that: The specific stabilizer combination includes a mixture of phosphate, carbonate and silicate, and the mass ratio of phosphate, carbonate and silicate is 1:1:

1.

9. A sodium hypochlorite production process based on a supported catalyst and an adsorbent according to claim 1, characterized in that: The method for modifying coconut shell activated carbon by concentrated nitric acid in step 5 comprises the following steps: a. stirring and mixing coconut shell activated carbon particles and a modifier aqueous solution, with a solid-liquid ratio of 1:10 to 1:8 and a temperature of the modifier aqueous solution of 15°C to 45°C; b. treating the stirred and mixed solution at a pressure of 0.2 MPa to 0.5 MPa for 1.5 hours to 4 hours; c. filtering the modified solution and washing it with deionized water until it is neutral to obtain modified activated carbon.